ePortfolio as a learning and assessment tool - Rodrigues, Maria Rosário (2019)
This paper falls within the ERASMUS+ KA2 project Empowering Eportfolio Process (EEP). This project aims to promote the development of best practices in Higher Education, by encouraging cooperation and sharing between teachers and researchers from several European countries using digital portfolios. The work so far has allowed us to systematize some reflections on the students’ perspective related to the use of digital portfolios as learning and evaluation tools. Among the conclusions of the project, we highlight the opinion students have built on the role of portfolios as a transforming element of evaluation processes, giving it a character of greater integration in learning. The students suggest that evaluation should be run more frequently and should meet their needs. This analysis was carried out by the Portuguese working group that promoted three collective interviews with students of several courses of the School of Education of the Polytechnic Institute of Setúbal (ESE-IPS). The analysis of the collected data allowed us to perceive the evaluation that the students attribute to the feedback and to the monitoring of their work by the teacher. We advocate that these aspects should be appropriated by teachers, thus promoting the quality of the process of learning and teaching in higher education.